PENERAPAN KONSELING KELOMPOK UNTUK MENINGKATKAN SELF-ESTEEM SISWA - Indrawati Indrawati (UNIB Press, 2021)
The purpose of this study was to describe the application of group counseling to improve self-esteem of students of class XI Science in SMA 3 Lahat. The research method used is classroom action research, which consists of three cycles. Research procedures are planning, implementation, observation and reflection. The research subjects were students of class XI IPA, amounting to 10 people consisting of 8 men and 2 women. Data collection techniques in this study used an observation sheet. Analysis of the data used is the mean (mean) which is then consulted with the assessment criteria, namely: 4 =Very Good, 3 = Good, 2 = Less, 1 = Very Less. The results showed that the application of group counseling services can improve student self-esteem